EVALUATION OF RAT LEYDIG CELL CULTURE COLLECTED WITH NYCODENZ GRADIENT IN PRODUCING TESTOSTERONE IN VITRO - Ekayanti Mulyawati Kaiin; Wahono Esthi Prasetyaningtyas (Universitas Syiah Kuala, 2017)
The aim of this study was to evaluate the ability of rat’s Leydig cells collected with Nycodenz gradient in producing testosterone in vitro. Leydig cells were collected using 5 column of Nycodenz gradient (4, 8, 10, 12, and 15%) and cells were evaluated regarding its concentration, viability, and purity of Leydig cells. Media used to cultured Leydig cells were Dulbecco’s Modified Eagle’s Medium (DMEM)+10% newborn calf serum (NBCS); DMEM+10% NBCS+2,5 IU/mL human chorionic gonadotrophin (hCG); DMEM+10% NBCS+ 5 µg/mL insulin, 10 µg/mL transferrin, and 5 µg/mL Se (ITS); DMEM+10% NBCS+hCG+ITS at 5% CO2 incubator with temperature of 37.5° C for 3 days. Culture medium was collected every day for testosterone analysis with enzyme-linked immunosorbent assay (ELISA). By adding ITS to the medium, Leydig cells concentration was significantly increased (8.92x106 cells/mL) compared to medium with serum (7.74x106 cells/mL) or hCG (7.68x106 cells/mL) (P0.05). ITS and hCG in medium significantly increased Leydig cells concentration (10.40x106 cells/mL) at day 3 of culture (P0.05). The result of parallelism test showed that the assay obtained good validity to measure testosterone concentration in culture medium. Testosterone in medium was detected at 1.80-2.60 ng/mL at day 1 of culture. In conclusion, Leydig cells collected with Nycodenz gradient had no effect to testosterone secretion from Leydig cells in vitro.